Weight–length and length–length relationships for reef fish species from the Cape Verde Archipelago (tropical north‐eastern Atlantic). (10th July 2014) - Oliveira, M. T.; Santos, M. N.; Coelho, R.; Monteiro, V.; Martins, A.; Lino, P. G.
Summary This study reports weight–length and length–length relationships for selected coastal reef fish species of the Cape Verde Archipelago (tropical north‐eastern Atlantic). Specimens were caught with different types of gear (long‐lines, hand‐lines, purse‐seines and traps) during commercial fishing activities and sampled during fish market operations. A total of 8328 individuals were sampled, representing 29 species from 14 Families. This study provides the first references on weight–length and length–length relationships for five and 23 fish species worldwide, for 10 and 24 species for the Eastern Atlantic and for 12 and 26 species for Cape Verde Archipelago, respectively. Additionally, it provides revised weight–length relationships for 11 species from Cape Verde waters.